School and class closures and adolescent mental health during the second and later waves of the COVID-19 pandemic in Finland: a repeated cross-sectional study - Arja Rimpelä; Heidi Kesanto-Jokipolvi; Anna Myöhänen; Lauri Heikonen; Sanna Oinas; Raisa Ahtiainen (BMC, 2023)
Abstract Background Since the start of the COVID-19 pandemic, several studies have shown deterioration of adolescents' mental health when comparing periods before and after the start of the pandemic when there were national school closures. Less is known of the following waves with more variation in school closures and their duration. We study here, if variation in school or class closures was related to adolescents' mental health, if the duration mattered, and if the relationships were gender sensitive. Methods All comprehensive schools in Finland were invited to participate. Students (grades 7-9, age 13-16 years) answered digitally in November-December 2020 (n = 41,041) and April-May 2021 (n = 28,501). The responses were given anonymously. Mental health was measured by daily health complaints and moderate/severe anxiety (GAD-7, only in 2021). School and class closures were combined to a variable (yes/no). The duration of a closure was analysed in weeks. Logistic regression analysis was used. Results In 2020, 14% of pupils reported a school closure and 33% in 2021. The gender-adjusted odds for daily health complaints were higher among those with the school or class closure compared to those without (OR = 1.2 (1.1-1.3) in 2020; OR = 1.3 (1.2-1.3) in 2021). For anxiety, the corresponding OR was 1.3 (1.2-1.4). Girls had higher odds for both measures than boys and the non-binary gender had the highest. A one-week increase in the duration of closure had a small effect on daily health complaints OR = 1.05 (1.02-1.09) in 2020; OR = 1.05 (1.02-1.08) in 2021) and anxiety OR = 1.05 (1.01-1.08). Gender differences in the associations of the school or class closure with mental health were negligible. Conclusions A specific negative influence of school or class closures on adolescents' mental health was seen when comparing those who had school/class closure and those who did not during the further waves of the pandemic. The duration of closure had a small effect, too. The non-binary gender had lowest mental health, but the influence of school closure on mental health was mainly similar between the genders. School closures are one of the factors in adolescents' mental health, but not the only one.